2015
DOI: 10.1371/journal.pone.0119305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relative Concentration of Ethanol and Other Odorous Compounds (OCs) Emitted from the Working Surface at a Landfill in China

Abstract: Estimating odor emissions from landfill sites is a complicated task because of the various chemical and biological species that exist in landfill gases. In this study, the relative concentration of ethanol and other odorous compounds emitted from the working surface at a landfill in China was analyzed. Gas sampling was conducted at the landfill on a number of selected days from March 2012 to March 2014, which represented different periods throughout the two years. A total of 41, 59, 66, 54, 63, 54, 41, and 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…al. (2012, Kim et al (2005) and Li et al (2005) has shown that dimethyl sulphide (DMS), as an odorant, can be a cause of odour nuisance problems in landfi lls.…”
Section: Introductionmentioning
confidence: 99%
“…al. (2012, Kim et al (2005) and Li et al (2005) has shown that dimethyl sulphide (DMS), as an odorant, can be a cause of odour nuisance problems in landfi lls.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol emissions can be found in the food and beverage industries, ethanol refineries and landfill sites . Atmospheric ethanol should be reduced because it is a volatile organic compound (VOC) . Excessive ethanol concentration (>2 g m −3 ) inhalation may cause health problems including irritation of respiratory system and conscience loss .…”
Section: Introductionmentioning
confidence: 99%
“…3 Atmospheric ethanol should be reduced because it is a volatile organic compound (VOC). 5 Excessive ethanol concentration (>2 g m −3 ) inhalation may cause health problems including irritation of respiratory system and conscience loss. 6,7 Methane as the second-most important GHG after CO 2 is 28-36 times more hazardous than CO 2 in terms of heat-trapping in a 100-yr time horizon based on global warming potential (GWP) index.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, the VOC concentration in landll gas varies in a comparatively large range and the related concentration adjustment is complex and cumbersome. 18 Thus, enhancement of the effective contact area is more popular. In real applications, an aeration device is usually employed to generate tiny bubbles and then disperse these bubbles in the liquid-phase evenly.…”
Section: Introductionmentioning
confidence: 99%